The activity of methylene blue against asexual and sexual stages of Plasmodium vivax - Fabbri, Camila; Quaresma Ramos, Glenda; Clarys Baia-da-Silva, Djane; Oliveira Trindade, Alexandre; Carlos Salazar-Alvarez, Luis; Costa Ferreira Neves, Juliana; Santos Bastos, Ivanildes dos; Guimarães Costa, Allyson; Vinicius Guimarães Lacerda, Marcus; Marcelo Monteiro, Wuelton; Trindade Maranhão Costa, Fabio; Costa Pinto Lopes, Stefanie (Frontiers in Cellular and Infection Microbiology, 2023)
Methylene blue (MB) is an alternative for combating drug-resistant malaria parasites. Its transmission-blocking potential has been demonstrated in vivo in murine models, in vitro, and in clinical trials. MB shows high efficacy against Plasmodium vivax asexual stages; however, its efficacy in sexual stages is unknown. In this study, we evaluated the potential of MB against asexual and sexual forms of P. vivax isolated from the blood of patients residing in the Brazilian Amazon. An ex vivo schizont maturation assay, zygote to ookinete transformation assay, direct membrane feed assay (DMFA), and standard membrane feed assay (SMFA) using P. vivax gametocytes with MB exposure were performed. A cytotoxicity assay was also performed on freshly collected peripheral blood mononuclear cells (PBMCs) and the hepatocyte carcinoma cell line HepG2. MB inhibited the P. vivax schizont maturation and demonstrated an IC50 lower than that of chloroquine (control drug). In the sexual forms, the MB demonstrated a high level of inhibition in the transformation of the zygotes into ookinetes. In the DMFA, MB did not considerably affect the infection rate and showed low inhibition, but it demonstrated a slight decrease in the infection intensity in all tested concentrations. In contrast, in the SMFA, MB was able to completely block the transmission at the highest concentration (20 µM). MB demonstrated low cytotoxicity to fresh PBMCs but demonstrated higher cytotoxicity to the hepatocyte carcinoma cell line HepG2. These results show that MB may be a potential drug for vivax malaria treatment.